Foreign Direct Investment, Energy Infrastructure and Manufacturing Output in Nigeria - Onabote, Ademola; Abuh, Ojamaliya; Emmanuel, Oduntun; Eseyin, Oluwasegun; Okafor, Victoria (International Journal of Energy Economics and Policy, 2021)
In recent years, developing countries like Nigeria with large human and natural resources have attracted huge investment leading to a rise in foreign investment into the Nigerian economy. To create the conditions that would attract more Foreign Direct Investment into the manufacturing subsector, the right infrastructure must be put in place. This study examined the relationship between Foreign Direct Investment, infrastructure and manufacturing output in Nigeria. Time series data between the periods of 1981-2016 was used. Johansen cointegration was used to assess the relationship between Nigeria’s foreign direct investment, infrastructure, and production efficiency. The result showed that the explanatory variables and the manufacturing production in Nigeria have a long-run relationship. The relationship between foreign direct investment, infrastructure and manufacturing production in Nigeria is also found to be significant and positive. Following the finding of the study, specific policy recommendations were made to improve energy infrastructure for the manufacturing sector and keep foreign investment flowing into the economy. Keywords: Foreign Direct Investment, Energy Infrastructure, Manufacturing output JEL Classifications: E22, F21, L60, O14 DOI: https://doi.org/10.32479/ijeep.9686